2008
DOI: 10.1111/j.1553-2712.2007.00022.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Clinical Effectiveness of Midazolam versus Propofol for Procedural Sedation in the Emergency Department: A Systematic Review

Abstract: Objectives: To synthesize the evidence comparing the adverse event (AE) profile and clinical effectiveness of midazolam and propofol for procedural sedation (PS) in adults in the emergency care setting. Methods:The authors conducted a systematic review of randomized controlled trials (RCTs) and observational studies reporting the use of either midazolam and ⁄ or propofol for adult PS in the emergency department (ED). A systematic search strategy was developed and applied to six bibliographic reference database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 45 publications
(97 reference statements)
1
36
0
Order By: Relevance
“…By far, the most commonly used agents in adults are propofol and midazolam. 7 In a previous analysis and systematic review, we concluded that the proportion of procedural success and the safety profiles of midazolam and propofol were not significantly different when used for adults for PS in the ED. 7 Because of this, a rational choice of which agent to use should be based on the cost of treatment.…”
mentioning
confidence: 82%
See 3 more Smart Citations
“…By far, the most commonly used agents in adults are propofol and midazolam. 7 In a previous analysis and systematic review, we concluded that the proportion of procedural success and the safety profiles of midazolam and propofol were not significantly different when used for adults for PS in the ED. 7 Because of this, a rational choice of which agent to use should be based on the cost of treatment.…”
mentioning
confidence: 82%
“…The reference population in this study represents patients who were enrolled in randomized controlled trials (RCTs) and prospective observational studies that were included in the analysis from which we derived estimates of clinical effectiveness and AEs. 7 The reference population consisted of adult patients who presented to the ED with an indication for routine PS, such as cardioversion or an orthopedic reduction. The patients were adults, had minimal comorbidities (American Society for Anesthesiology Grade I or II), and were pretreated with a short-acting narcotic before PS.…”
Section: Study Setting and Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…Hohl CM., provided effectiveness of midazolam versus propofol for 2574 patients undergoing a variety of endoscopic procedures and found a better safety profile of bensodiasepines. Clarke et al also report a beter safety profile of bensodiasepines in over 28000 patients (5). All patients who were in our study who underwent the endoscopic procedure in day-case settings were exceptionally satisfied, thanks to administration of procedural sedation and analgesia.…”
Section: Table1 Individual List Of Patient Satisfactionmentioning
confidence: 76%